A personal reflection upon navigating into a senior academic role - Idowu, Bernadine D. (Frontiers in Sociology, 2023)
There are 22,795 University professors in the UK, 6,340 are women and only 40 are Black women, Asian women are a few more in number. This clearly demonstrates the uncommon narrative of the underrepresentation of Black Minority Ethnic (BME) academics in Higher Education (HE) which has been written about in detail. In contrast, it is rare to read reports on initiatives to successfully navigate senior academic posts. In this paper I will describe two initiatives that I have developed and organised to successfully navigate senior BME academic posts, which has impacted my journey. The first initiative was to understand why postdoctoral researchers were “post-docing” for years, having not been successful in making the transition to lecturers. What was hindering the transition? I was one of them, so also some of my female peers, who incidentally left HE. I was determined not to leave. I again thought about how to tackle it. It is a known fact that hearing successful BME people experiences and journeys also understanding how they navigated HE, can be powerful. In addition, empowering oneself with additional skills including mentoring, networking, also applying for positions and not excluding ourselves due to the lack of confidence, finally the importance of having a work life balance is important; after all health is wealth. I used this to put together the BME Early Career Researcher (ECR) conference - How to Stay in Academia. Six years later it is still going strong. In this paper I will share the impact made over the years which will include testimonies and promotions, including my recent promotion to an Associate Professor. The second initiative was to understand the barriers and challenges of Senior lecturers being promoted to Reader and Professors. Having successfully transitioned to a lecturer, being overlooked for promotion was now an issue. The project was conducted in 2016/17 at KCL as part of the action plans that needed to be delivered having been a recipient of the Bronze Race Equality Charter Mark. Ices.